Socially inclusive infrastructure for disaster risk reduction in urban planning: insights from the SADC region - Lunga, Wilfred; Malandela, Gcina; Kaifa, Jane M.; Baloyi, Caiphus; Musarurwa, Charles; Ramoroka, Tlou; Kunguma, Olivia (Frontiers in Built Environment, 2025)
IntroductionThe accelerating pace of urbanization in the 21st century has intensified the need for inclusive and resilient infrastructure development, particularly in the face of rising socio-economic inequalities and escalating disaster risks. This study explores the integration of social equity dimensions and Disaster Risk Reduction (DRR) principles within urban planning frameworks as a pathway toward sustainable and resilient urban futures.MethodsA qualitative research design was adopted, drawing on a triangulated methodology that includes document analysis, an extensive literature review, and selected case studies on urban planning practices. These methods were employed to interrogate current urban development paradigms and assess the extent to which equity and resilience are operationalized in planning processes.ResultsFindings indicate that, despite growing theoretical advancements in equitable and risk-sensitive urban development, significant systemic challenges remain. These include limited community participation in planning processes, persistent institutional silos, and resource constraints that hinder transformative action. The analysis further reveals that current urban governance mechanisms often lack the capacity to meaningfully integrate long-term resilience and equity considerations.DiscussionIn response to these challenges, the study recommends a paradigm shift in urban planning towards the adoption of future-oriented and participatory approaches. Key policy recommendations include: (1) embedding equity-focused DRR strategies within urban development policies; (2) fostering multi-stakeholder collaboration to bridge institutional divides; and (3) mainstreaming anticipatory and inclusive planning models in urban governance systems. Such integrative approaches are essential for aligning infrastructure development with the broader goals of social justice, environmental sustainability, and urban resilience.